Penerapan Layanan Konseling Individual dengan Pendekatan Mauidzah Al-Hasanah dalam Mengatasi Perilaku Membolos Peserta Didik Kelas X MAS Al Washliyah 22 - Filja, Padiahani (ALSYS, 2025)
This study aims to evaluate the implementation of individual counseling services with the Mauidzah Hasanah approach in overcoming truancy behavior of class X students at MAS Al-Wasliyah 22. Truancy behavior is a form of deviation that affects the learning process and academic achievement of students. The Mauidzah Hasanah approach, which is based on gentle and wise verbal communication, was chosen to provide advice and guide students more effectively and touch on their moral aspects. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The subjects of the study included a guidance and counseling teacher who implemented individual counseling services and seven class X students who had a history of truancy behavior. The results showed that the implementation of individual counseling based on Mauidzah Hasanah had a positive impact on changes in student behavior. The guidance and counseling teacher began by building a warm and open relationship, so that students felt comfortable expressing their problems. Advice and motivation given in a gentle and empathetic manner were able to encourage students to reflect on their life goals, understand the importance of discipline, and improve their attitudes towards learning. As a result, students showed increased awareness, motivation, and self-confidence. This study recommends the implementation of counseling services based on Mauidzah Hasanah values ​​as one of the solutions to overcome student deviant behavior in the school environment.